PERANCANGAN SISTEM INFORMASI IN OUT STOCK BERBASIS WEB DENGAN FRAMEWORK CODEIGNITER PADA TOKO METROCHILON PAPUANA GEMILANG (MPG) WOSI : PERANCANGAN SISTEM INFORMASI IN OUT STOCK BERBASIS WEB DENGAN FRAMEWORK CODEIGNITER PADA TOKO METROCHILON PAPUANA GEMILANG (MPG) WOSI - Dhian Pramana Aschary; Christian Dwi Suhendra; Bertha Pangaribuan (JISTECH: Journal of Information Science and Technology, 2024)
With the aim of overcoming management and storage problems that still use manual methods in storing data, products, incoming goods, and outgoing goods along with each existing report. It is felt to be less effective and inefficient, because if there is an addition to product data, incoming goods, outgoing goods along with each data report must be studied in detail as a whole, so as to provide ineffectiveness in data processing and storage. The impact of this problem is the delay in providing reports to business owners. and with the existence of an application system "Designing a Web-Based In Out Stock Information System with Codeigniter Framework at the Metrochilon Papuana Gemilang (MPG) Wosi Store". With the mechanism of the in out stock application system, the company gets stock data of goods that are still available to then be used as a reference for incoming and outgoing goods, the issuance of goods is more systematic. With this mechanism, it is proven to help the company's performance and overcome problems in accordance with current technological developments.